Pengaruh Open Kinetic Chain Exercise Tehadap Peningkatan Kemampuan Fungsional Pada Kondisi Osteoarthritits Knee di RSUD Gambiran Kota Kediri - Asiyah Binti Supri Astuti; Nurul Halimah; Puspo Wardoyo; Angria Pradita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Osteoarthritis of the knee is a degenerative joint disease that causes limited joint mobility. Due to limited joint mobility, it can cause a decrease in the functional ability of the knee. Open kinetic chain exercise is a movement that can increase the working power of the quadriceps and hamstring muscles as a component to stabilize the knee joint to improve walking patterns so as to increase the functional ability of the knee. The purpose of this study was to determine the effect of giving open kinetic chain exercise to increase functional ability in the condition of knee osteoarthritis. This research used a qualitative-experimental method with one group pretest and posttest design. sampling used simple random method and obtained 30 respondents. Instrumen used was Womac Scale Measuring Instrument with an open kinetic chain exercise design, given 2 times a week for a month. Statistical test was used Wilcoxon and the result was median value of pre 35.4 and post 31.7 with a difference of 3.7. P-value was 0.001 (<0.05), which mean there is an effect of open kinetic chain exercise with 8 treatments on increasing functional ability in knee osteoarthritis conditions.Keywords: knee osteoarthritis; open kinetic chain exercise; functional abilityABSTRAKOsteoarthritis knee merupakan penyakit degenerative sendi yang menyebabkan mobilitas sendi menjadi terbatas. Akibat keterbatasan mobilitas sendi dapat menyebabkan menurunnya kemampuan fungsional lutut. Open Kinetic Chain Exercise merupakan gerakan yang dapat meningkatkan daya kerja otot quadrisep dan hamstring sebagai komponen untuk menstabilkan sendi lutut untuk memperbaiki pola jalan sehingga dapat meningkatkan kemampuan fungsional lutut. Tujuan penelitian ini untuk mengetahui pengaruh pemberian Open Kinetic Chain Exercise terhadap peningkatan kemampuan fungsional pada kondisi osteoarthritis knee. Jenis penelitian ini menggunakan kualitatif eksperimen dengan metode one group pretest and posttest design. Dengan populasi 30 orang yang diambil secara acak. Menggunakan alat ukur skala womac dengan desain latihan open kinetic chain exercise diberikan sebanyak 2 kali seminggu selama sebulan. Uji hipotesis wilcoxon diperoleh nilai median pre 35,4 dan post 31,7 dengan selisih 3,7. Sehingga, nilai P sebanyak 0,001 < 0,005. Maka ditarik kesimpulan, terdapat pengaruh pemberian open kinetic chain exercise selama 8 kali perlakuan terhadap peningkatan fungsional pada kondisi osteoarthritis knee.Kata kunci: osteoarthritis knee; open kinetic chain exercise; kemampuan fungsional